2018
DOI: 10.1002/14651858.cd003313.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin for alloimmune hemolytic disease in neonates

Abstract: Analysis 3.1. Comparison 3 Intravenous immunoglobulin (IVIg) plus phototherapy versus phototherapy. IVIg administration ≤ 12 hours after birth, Outcome 1 Use of exchange transfusion (≥ 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 52 publications
1
56
0
5
Order By: Relevance
“…7 More recently, based on all included studies a Cochrane review by Zwiers C et al, in 2018 could make no conclusions on the benefit of IVIG in preventing ET or top-up transfusion and therefore routine use in alloimmune HDN is not recommended. 8 In this study Exchange transfusion rates have shown a decreasing trend with an increase in IVIG usage during these 3.5 years as shown in Fig 1. The reason for apparent reduction in ET rates may not necessarily be IVIG alone but earlier recognition and better management, including effective intensive phototherapy and supportive care. When authors tried to check for a possible comparative group, we found that during this study period there were 91 neonates with hemolytic disease with Serum Bilirubin (SBR) in nearexchange range as shown in Table 2.…”
Section: Discussionmentioning
confidence: 50%
“…7 More recently, based on all included studies a Cochrane review by Zwiers C et al, in 2018 could make no conclusions on the benefit of IVIG in preventing ET or top-up transfusion and therefore routine use in alloimmune HDN is not recommended. 8 In this study Exchange transfusion rates have shown a decreasing trend with an increase in IVIG usage during these 3.5 years as shown in Fig 1. The reason for apparent reduction in ET rates may not necessarily be IVIG alone but earlier recognition and better management, including effective intensive phototherapy and supportive care. When authors tried to check for a possible comparative group, we found that during this study period there were 91 neonates with hemolytic disease with Serum Bilirubin (SBR) in nearexchange range as shown in Table 2.…”
Section: Discussionmentioning
confidence: 50%
“…Intravenous immunoglobulin (IVIG) remains a recommended treatment modality for neonatal isoimmune hemolytic disease if total serum bilirubin continues to rise despite intensive phototherapy [ 8 ]. However, although some reports suggested a reduction in the need for exchange transfusion after IVIG administration, the practice remains controversial because most clinical trials were not blinded and a recent systematic meta-analysis suggested overall poor quality of evidence and an unknown benefit effect estimate [ 41 ]. In nonneonatal populations, IVIG has been rarely associated with worsening of hemolysis [ 42 ]; if this phenomenon is present in the neonatal population, there is the possibility of actually worsening jaundice from IVIG therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Supported by these recommendations by the AAP, there was a significant increase in IVIG use in severe hyperbilirubinemia due to AIHD. A recent Cochrane review by Zwiers et al was done in 2018, to further evaluate this practice’s evidence-based aspects [ 55 ]. In their meta-analysis, 27 full-text articles were screened for eligibility.…”
Section: Clinical Use In Fetuses and Neonatesmentioning
confidence: 99%